Application Of Back Massage Therapy To Reduce Pain In Gastritis Patients Through The Application Of Peplau's Theory At Lingkar Timur Community Health Center Bengkulu, 2025 - Lestari, Rapita; Susanti , Meri Epriana (Jurnal Kesehatan Mitra Sekawan, 2026)
Gastritis  is  defined  as  pain  or  discomfort  in  the  upper  abdomen.  Patients  with  gastritis  or  stomach  ulcers  usually  present  with  additional  complaints  ranging  from  nausea  to  vomiting.  Other  symptoms  such  as  bloating,  early  satiety,  decreased  appetite,  and  frequent  belching  may  also  occur.The  purpose  of  this  study  is  to  apply  back  massage  therapy  to  reduce  pain  in  gastritis  patients  through  the  application  of  Peplau's  theory  within  the  working  area  of  Lingkar  Timur  Community  Health  Center,  Bengkulu  City,  in  2025.The  method  used  in  this  final  nursing  case  study  involved  two  gastritis  patients  from  the  working  area  of  Lingkar  Timur  Community  Health  Center,  Bengkulu  City.  Nursing  care  was  provided  over  three  sessions.The  results  obtained  after  the  intervention  showed  that  back  massage  therapy  effectively  reduced  pain  levels  in  gastritis  patients.  Pain  scale  decreased  from  6  before  the  intervention  to  0  after  back  massage  therapy.It  can  be  concluded  that  there  is  a  significant  effect  of  back  massage  therapy  on  reducing  pain  in  patients  with  gastritis.  The  researcher  recommends  that  gastritis  sufferers  within  the  working  area  of  Lingkar  Timur  Community  Health  Center  adopt  back  massage  therapy  to  help  reduce  and  eliminate  pain.